2021
DOI: 10.1007/s10565-021-09678-x
|View full text |Cite
|
Sign up to set email alerts
|

The cytotoxicity of zinc oxide nanoparticles to 3D brain organoids results from excessive intracellular zinc ions and defective autophagy

Abstract: Cytotoxicity caused by high levels of ZnO NPs (64 μg/mL) correlated with high intracellular Zn ion levels but not superoxide levels. Exposure to a noncytotoxic concentration of ZnO NPs (16 μg/mL) increased the autophagy-marker proteins LC3B-II/I but decreased p62 accumulation, whereas a cytotoxic concentration of ZnO NPs (64 μg/mL) decreased LC3B-II/I proteins but did not affect p62 accumulation. Fluorescence micro-optical sectioning tomography revealed that 64 μg/mL ZnO NPs led to decreases in LC3B proteins t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…Human iPSC-derived neurons-based 3D brain organoids containing a variety of neurons and glial cells possess a more complete organization and are more similar to the human central nervous system [ 57 ]. The toxic effects of silver nanoparticles [ 58 ] and zinc oxide nanoparticles [ 59 ] have been investigated using brain organoids. Researchers also use MEA [ 60 ] and whole-cell patch-clamp [ 61 ] to record brain organoids’ electrophysiological response to external stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Human iPSC-derived neurons-based 3D brain organoids containing a variety of neurons and glial cells possess a more complete organization and are more similar to the human central nervous system [ 57 ]. The toxic effects of silver nanoparticles [ 58 ] and zinc oxide nanoparticles [ 59 ] have been investigated using brain organoids. Researchers also use MEA [ 60 ] and whole-cell patch-clamp [ 61 ] to record brain organoids’ electrophysiological response to external stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial injury and oxidative stress caused by impaired autophagy flux ultimately result in cell death. [ 83 ] Liu et al [ 35 ] found that low doses of ZnONPs (16 μg/mL) induced autophagy and reduced p62 accumulation. In contrast, high doses of ZnONPs (64 μg/mL) caused defective autophagy and elevate intracellular levels of Zn 2+ , resulting in cytotoxicity.…”
Section: Autophagy Regulation By Inorganic Npsmentioning
confidence: 99%
“…30 Different from several inorganic piezoelectric nanomaterials mentioned above, ZnO nanomaterials exhibited inhibitory effects on nerve cells at subtoxic concentrations (10 −4 -10 −1 μg/ mL). 31,32 Therefore, the integration with polymer materials and the surface modification of nanoparticles are often used to reduce the biological toxicity of inorganic ZnO nanoparticles, and the ZnO-based biomaterials have been used in the repair of PNI, drug delivery, and bioimaging. [33][34][35] It's worth mentioning that ZnO-based wound dressings can accelerate the healing process of chronic wounds due to the antibacterial properties and piezoelectric properties of ZnO nanomaterials.…”
Section: Inorganic Piezoelectric Nanomaterialsmentioning
confidence: 99%
“…With the US‐driven piezoelectric effect, pheochromocytoma cells (PC12 cells) treated with BN nanotubes showed increased neurites, indicating the application prospect in ES of nerve tissue engineering 30 . Different from several inorganic piezoelectric nanomaterials mentioned above, ZnO nanomaterials exhibited inhibitory effects on nerve cells at subtoxic concentrations (10 −4 –10 −1 μg/mL) 31,32 . Therefore, the integration with polymer materials and the surface modification of nanoparticles are often used to reduce the biological toxicity of inorganic ZnO nanoparticles, and the ZnO‐based biomaterials have been used in the repair of PNI, drug delivery, and bioimaging 33–35 .…”
Section: Classification Of Piezoelectric Biomaterialsmentioning
confidence: 99%